Reading skill profiles and their phonological and linguistic precursors in adolescents with oral and written language difficulties - Aguilar-Mediavilla, Eva; Buil-Legaz, Lucía; Mateus-Moreno, Angélica; Esteller-Cano , Àngels; Adrover-Roig , Daniel (Revista de Investigación en Logopedia, 2025)
People with Developmental Language Disorder (DLD) and Reading Difficulties (RD) experience reading problems during primary education. According to the Simple View of Reading, deficits in oral comprehension affect reading comprehension, while phonological processing issues impact decoding. This study aims to: (1) longitudinally compare the decoding and reading comprehension profiles in Catalan-Spanish bilinguals with DLD, RD, and Typical Development (TD) from primary to secondary education; and (2) examine how reading skills, phonological memory, verbal fluency, and oral language at age 10 predict reading skills at age 14. The sample included 77 adolescents aged 10 to 14: DLD (n = 15), RD (n = 33), and TD (n = 29). At age 10, oral language, phonological and semantic fluency, and phonological working memory were assessed. Decoding and reading comprehension were evaluated at ages 10 and 14. Both DLD and RD groups showed poorer decoding skills compared to the TD group at both time points, although all groups improved over time. In reading comprehension, the DLD group scored significantly lower than the RD and TD groups. Semantic fluency at age 10 predicted decoding at age 14, while oral language predicted reading comprehension. The DLD group exhibits persistent difficulties in both decoding and reading comprehension, whereas the RD group shows primarily decoding challenges. Decoding, oral language skills and semantic fluency in primary education are key predictors of reading performance in secondary education.
Keywords: Comprehension; Fluency; Language disorder: Longitudinal study; Reading